Analisis Strategi Pemasaran Teh Celup Walini Industri Hilir PTPN VIII Berdasarkan Perspektif Syariah - Sopandi, Hendra; Miftahudin (Ikatan Da'i Indonesia, 2024)
PT Perkebunan Nusantara (PTPN) VIII's downstream company is the Downstream Tea Industry (IHT). IHT makes two types of tea: tea bags and brewed tea. The trademark used is Walini. Every year, IHT in running its business increases. This makes the author interested in examining the methods used and whether these methods are in accordance with sharia principles. Qualitative descriptive research is used in this type of research. Both primary and secondary data were used. Primary data was obtained from the marketing division, sales division, tabin, general department employees, and head of production. Data collection methods are through interviews, documentation, and observation. The results showed that IHT uses a marketing mix strategy, which includes product, price, location, and promotion strategies. The product strategy is to maintain quality, increase flavor variety, and improve packaging. The price strategy is Cost-Plus, Premium, Dynamic, and Competition-Based. The place (distribution) strategy is e-commerce, general trade, and contemporary trade. She uses gimmicks, collaborating with private and public educational institutions, events, and social media to promote herself. IHT uses sharia marketing strategies by using attributes and values such as spirituality, shidiq, amanah, fathanah, and tabligh.